2021
DOI: 10.1039/d1nj04534b
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the metal ion release and antibacterial activity of ZnO@ZIF-8 by modulating its synthesis method

Abstract: An excellent feature of [ZnO]0.181@ZIF-8 is its slower release of Zn2+ ions as compared to Zn(CH3COO)2.2H2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The MOF nanomaterials exhibited exceptional antibacterial effect, particularly ZIF-67 43 . This is attributed to their porous structure and their ability to function as a source of metal ions 13 , 44 . Interestingly, Zheng et al have attributed the antibacterial activity of ZIF-67 MOF to a chemical interaction mechanism through the ROS and found that ZIF-67 has a promising antibacterial activity against Gram-negative bacteria E.coli in destroying the bacterial membrane solutions 13 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The MOF nanomaterials exhibited exceptional antibacterial effect, particularly ZIF-67 43 . This is attributed to their porous structure and their ability to function as a source of metal ions 13 , 44 . Interestingly, Zheng et al have attributed the antibacterial activity of ZIF-67 MOF to a chemical interaction mechanism through the ROS and found that ZIF-67 has a promising antibacterial activity against Gram-negative bacteria E.coli in destroying the bacterial membrane solutions 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The Co 2+ ions that are present in the ZIF-67 MOF NPs have the ability to cause cell wall rupture by generating ROS mediated toxicity 13 . This structural changes and deformation in the bacterial cell wall lead to damages in the intracellular components, proteins, phosphate amine and fatty acid groups of the peptidoglycan in the bacterial cell wall 41 , 44 . Instantaneously, a complete breakdown of the glycan backbone and the phospholipid in addition to a DNA damage upon the exposure of the nanoparticles to the nucleus 40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, traditional ZIF-8 can also release zinc ions and 2-methylimidazole to kill E. coli effectively under a variety of environmental conditions [ 19 ]. However, light-driven inactivation of bacteria as a photocatalyst is the main source of antibacterial ability in traditional ZIF-8 [ 20 , 21 , 22 ]. However, ZIF-8 has not been directly used to inhibit Gram-positive S. aureus to date.…”
Section: Introductionmentioning
confidence: 99%